Preliminary characterization of plga scaffold for interverterbral discs tissue engineering - Mohamad, Mohd Yusof; Md Nazir, Noorhidayah; Abdul Rahman, Rozlin; Mohamad Syukri, Norhamiza; Ahmad Radzi, Muhammad Aa'zamuddin; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Poly(lactic-co-glycolic acid) or (PLGA) has attracted considerable interest for biomedical applications due to its biodegradability and approval for clinical use. This study aimed to characterize PLGA in terms of swelling capacity, compression test and scanning electron microscopy (SEM). The PLGA scaffold was fabricated using the solvent casting, salt leaching technique. For swelling test, the scaffolds were subjected to soaking in water for 48 hours. Compression test was performed using Instron E300 Machine. Results indicated that PLGA had swelling ability more than 100% [201.82%±48.51]. Compressive strength of PLGA showed average load of 84.01N±39.33. SEM demonstrated interconnected pores in the scaffold. Further tests need be done to characterize PLGA and its combination with other materials in terms of degradation and thermal properties.